Features of the History of a Phenomenon and a Theory - Zambrano Leal, Armando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
From the beginning of the French Revolution and well into the XX century, the history of the French school system is marked by three important characteristics: it is free of charge, compulsory, and democratic. This last condition will give birth to school failure, an important sociological category. This category is a product, on the one hand, of sociologists' critique of the power of psychology and psychotherapy in the school space, and on the other, it is the result of important statistic studies beginning in 1950. During almost four decades, classical sociology dominated research on this phenomenon. Nevertheless, towards 1987, a new theory emerged known as relation to knowledge, theoretically based on anthropology, psychoanalysis and social anthropology. The present researchbased article situates historical elements for understanding school failure as a sociological phenomenon and relation to knowledge as theory.